2022
DOI: 10.1007/s40857-021-00260-3
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Face Masks on Verbal Communication in Persian in the Presence of Background Noise in Healthcare Staff

Abstract: Wearing face masks has resulted in verbal communication being more challenging during the COVID-19 pandemic. This study aimed to investigate the effect of face masks on the speech comprehensibility of Persian nurses in healthcare settings. Twenty female nurses from the governmental hospitals randomly participated in an experiment on seven typical commercial face masks at two background noise levels. Nurses' speech intelligibility from a human talker when wearing each face mask was determined based on the speec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…The disparity in results may be attributed to the current study being conducted during the pandemic, which necessitated the use of face masks. Similarly, Aliabadi et al (39) reported varying decreases in speech intelligibility among nurses using different types of personal protective equipment (PPE), such as surgical masks and face shields.…”
Section: Discussionmentioning
confidence: 99%
“…The disparity in results may be attributed to the current study being conducted during the pandemic, which necessitated the use of face masks. Similarly, Aliabadi et al (39) reported varying decreases in speech intelligibility among nurses using different types of personal protective equipment (PPE), such as surgical masks and face shields.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic led to massive changes and restrictions in everyday life and brought significant uncertainties regarding the delivery of mental health services. Particularly in the field of mental health care, professionals faced a major challenge, as wearing a face mask was associated with significant limitations in verbal and non-verbal communication on both the patient and therapist side [1][2][3]. In particular, non-verbal communication restricted by the mask [4] appeared to be particularly problematic in the psychotherapeutic context, as non-verbal behavior (facial expressions, gestures, and posture) has been shown in previous research to be essential for the development of an affective bond between patient and therapist and thus, among other factors, for the development of a working alliance [5,6].…”
Section: Introductionmentioning
confidence: 99%